2007
DOI: 10.4319/lo.2007.52.5.2013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of ice phenology trends across the Laurentian Great Lakes region during a recent warming period

Abstract: We examined spatial patterns of trends in ice phenology and duration for 65 waterbodies across the Great Lakes region (Minnesota, Wisconsin, Michigan, Ontario, and New York) during a recent period of rapid climate warming . Average rates of change in freeze (3.3 d decade 21 ) and breakup (22.1 d decade 21 ) dates were 5.8 and 3.3 times more rapid, respectively, than historical rates for Northern Hemisphere waterbodies. Average ice duration decreased by 5.3 d decade 21 . Over the same time period, average fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
144
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(166 citation statements)
references
References 41 publications
(48 reference statements)
17
144
1
4
Order By: Relevance
“…The lack of pronounced winter oxygen declines in surface samples of Allequash Lake, Crystal Lake, and Trout Bog could be explained by a combination of winter photosynthesis and low aerobic respiration. A more integrated understanding of winter oxygen dynamics across diverse lakes combined with ice phenology trends (Jensen et al 2007;Magnuson et al 2000) may increase understanding about the biogeochemical consequences of a changing winter.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of pronounced winter oxygen declines in surface samples of Allequash Lake, Crystal Lake, and Trout Bog could be explained by a combination of winter photosynthesis and low aerobic respiration. A more integrated understanding of winter oxygen dynamics across diverse lakes combined with ice phenology trends (Jensen et al 2007;Magnuson et al 2000) may increase understanding about the biogeochemical consequences of a changing winter.…”
Section: Discussionmentioning
confidence: 99%
“…Austin and Colman, 2007;Hook, 2009, 2010;Lenters et al, 2012) have shown that many lakes are getting warmer more rapidly than the ambient air temperature and more work is needed to explain these differences. This warming trend also affects the onset of freezing and duration of ice cover of many lakes, especially in northern latitudes and mountainous regions (Jensen et al, 2007;Dibike et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the approximately sinusoidal form of the air temperature curve, the dates on which the air temperature falls below and rises above 0°C, which are crucial for the timing of ice-on and ice-off, respectively, are not linear functions of air temperature. Instead, they are arc cosine functions of air temperature, which implies that the sensitivity of the timing of ice-on, the timing of ice-off, and the duration of ice cover are greater in warmer regions than in colder regions, and so will increase as the climate warms (Weyhenmeyer et al 2004a(Weyhenmeyer et al , 2011Jensen et al 2007;Livingstone and Adrian 2009). Thus, in the North Sea region, the impact of climate warming on lake ice phenology will be disproportionately large in those areas where winters are mild or variable and the duration of ice cover on lakes is already short (i.e.…”
Section: Lake Ice Phenologymentioning
confidence: 99%